Writing Learning Model Based on Écriture Automatique Method in Course Aufsatz I - Kharis, M. (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
This study aims to describe the process and results of implementing the Écriture Automatique writing method in the Aufsatz I course. Specifically, it presents the findings based on data collected through questionnaires. The study indicates that the Écriture Automatique method encourages students to write, stimulates their creativity, and helps them elaborate their ideas. Based on the students’ writing activities across two class meetings, the average scores ranged from 80.1 to 84.1 out of a maximum score of 100, both of which fall into the good category.